Terapi kombinasi dengan tusukan laser dan bantuan kursi roda pada kasus kelumpuhan kaki belakang seekor kucing - Soesatyoratih, Rr (ARSHI Veterinary Letters, 2023)
A male cat named Kucil was brought by his owner to the Cimanggu Animal Clinic with complaints that the animal was unable to stand on its hind legs. The results of the physical examination showed that the cat Kucil was unable to walk, urinate, and defaecate, and paralysed in the tail and hind legs. Radiographic examination revealed a buildup of faeces in the colon and narrowing of the lumbar intervertebral spaces 5-6 and 6-7. The Cat was diagnosed with Intervertebral Disc Disease (IVDD). Acupuncture therapy using laser puncture at points ST-36, GB-34, BL-35, BL-54, SP-10, and Hua Tuo Jia-Ji, assisted by the use of a wheelchair, is an option for treating neurological disorders in this case. Improvement in the condition resulting from the therapy occurred after the 2nd therapy. To support the use of a wheelchair applied to the cat until the 4th therapy, the cat appears to be able to move its hind legs, and after the 9th therapy the cat appears to be able to walk.